Ghrelin's role as a major regulator of appetite and its other functions in neuroendocrinology. - Lim, C; Kola, B; Korbonits, M; Grossman, AB (2010)
Ghrelin is a circulating growth-hormone-releasing and appetite-inducing brain-gut peptide. It is a known natural ligand of the growth hormone secretagogue receptor (GHS-R). Ghrelin is acylated on its serine 3 residue by ghrelin O-acyltransferase (GOAT). The acylation is essential for its orexigenic and adipogenic effects. Ghrelin exerts its central orexigenic effect through activation of various hypothalamic and brain stem neurons. Several new intracellular targets/mediators of the appetite-inducing effect of ghrelin in the hypothalamus have recently been identified, including the AMP-activated protein kinase, its upstream kinase calmodulin kinase kinase 2, components of the fatty acid pathway and the uncoupling protein 2. The ghrelin/GOAT/GHS-R system is now recognised as a potential target for the development of anti-obesity treatment. Ghrelin regulates the function of the anterior pituitary through stimulation of secretion not only of growth hormone, but also of adrenocorticotrophin and prolactin. The implication of ghrelin and its receptor in the pathogenesis of the neuroendocrine tumors will also be discussed in this review.